Potential of Practice-Based Entrepreneurship Learning Model in Fostering Entrepreneurship Attitudes - Susilo, Agus; Aisya, Novia (Proceedings International Conference on Education Innovation and Social Science, 2022)
Currently, entrepreneurship learning has been recognized, particularly on its significant impact on the inculcation of entrepreneurship skills in educational program. Despite number of studies have been carried out to evaluate the implementation of entrepreneurship learning in higher education, the fact indicates the practices is merely preoccupied on the theory and design of entrepreneurship. This study focused to reveal the other side of the implementation of entrepreneurship education in higher education and aimed to determine the implementation of practice-based entrepreneurship learning in fostering students’ attitudes toward entrepreneurship. In-depth study through observation, interview and documentation, was done during entrepreneurship lectures that are designed in accordance with practice-based learning model. The findings of this study indicate that the students’ attitudes toward entrepreneurship improved during the practice-based entrepreneurship learning. They were relatively optimistic during the learning program. Furthermore, they had initiative attitude to facilitate entrepreneurship practice and achievement motive to gain better results, particularly to follow-up their design and experiences. Leadership skills also enhanced as indicated by their courage to be different with innovation and product creation, as well as to take risks.